Pemahaman Peserta Didik Mengenai Dampak Penggunaan Gadget - Muslimah, Shinta; Putra, Fuaddhilah; Chandra, Yasrial (Indonesian Journal of Counseling and Development, 2024)
This research was prompted by observations of students exhibiting various unfocused behaviors during class, such as playing games, taking photos, and using social media. Additionally, some students struggled with socializing and maintaining concentration while learning. The study aimed to describe students' understanding of: 1) the positive impacts of gadget use, and 2) the negative impacts of gadget use. Employing a quantitative descriptive analysis method, this research included a population of 42 students. Total sampling was used to select participants, and data was collected via questionnaires. The findings reveal that students' understanding of the positive impacts of gadget use was in the "fairly high" category, with 64.29% of respondents demonstrating this level of understanding. Similarly, their understanding of the negative impacts of gadget use was also categorized as "fairly high," at 88.10%. Overall, the study conducted at SMP Negeri 5 Sungai Limau, Padang Pariaman Regency, found that students' understanding of the impacts of gadget use was "fairly high," with a combined percentage of 88.10%. This indicates that most students have a good grasp of both the positive and negative consequences of using gadgets. Nevertheless, there's still an opportunity to further educate students on how to use gadgets wisely to minimize potential negative effects